Landuse Changes in Pancor Village, Selong District, East Lombok Regency 2019-2023 - Mulawarman, Rahmat; Iemaaniah, Zuhdiyah Matienatul (JPG (Jurnal Pendidikan Geografi), 2024)
Land use changes have positive and negative sides. Land use changes are influenced by population growth, thereby increasing the area of settlement area and other buildings as supporting facilities around settlements. Agricultural land is productive land that is used for staple food production and is subject to land conversion. The reduction in agricultural land results in reduced agricultural production which can threaten food security. In addition, land conversion is increasing, having a negative impact on the surrounding environment. The aim of this research was to determine land use changes in Pancor Village in the last 5 years. This research was carried out in Pancor Village by collecting field data obtained through the East Lombok ATR/BPN service and carrying out spatial analysis using ArcGIS 10.8. The results of the research show that in the last five years there has been a decrease in the area of rice fields by 33.8 hectares, fields/moors by 2.275 hectares, plantations by 0.035 hectares, while settlements and built-up land have increased by 36.11 hectares